Impacto da orientação nutricional em resultados de ciclos de reprodução assistida - Halpern, Gabriela; Arantes Sardinha, Fátima Aparecida; Setti, Amanda; Iaconelli Jr., Assumpto; Borges Jr., Edson [UNESP] (GN1 Sistemas e Publicacoes, 2013)
Infertility affects a high percentge of couples of reproductive age,stimulating tion Techniques (ART).Several factors may interfere with the success rates of ART. This paper aimed to evaluate the influence of diet on the success of assisted reproduction. Sixty couples undergoing cycles of intracytoplasmic sperm injection (ICSI) in a private assisted reproduction center participated in the study. The Participants were divided into groups: Control - n = 28 (did not received nutritional counseling) and Consultation - n = 32 (received nutritional counseling). It was used Student's t test or Mann-Whitney, chi-square test or Fischer. The results regarding the influence of chance in feeding habits with reproduction cycles were expressed as odds ratios and p values, considering p <0.05. The normal fertilization (81.0% and 67.1% p = 0.0225) and pregnancy rates (46.9% and 28.6% p = 0.0396) were significantly higher in patients who received nutritional counseling. Patients who had received guidance was twice as likely to become pregnant than those who had not received any guidance (OD: 2.27, p = 0.0408). Moreover, among these women, those who received nutritional counseling less than 60 days prior to the transfer of the embryos were nearly five times more likely to become pregnant (OD: 4.8, p = 0.036). There was change in eating behavior of patients who received nutritional counseling. It is possible to conclude that women who received nutritional counseling were more likely to successful pregnancy. © Todos os direitos reservados a.
Nutritional counseling impact on assisted reproduction treatment outcomes
Keywords: Assisted reproduction; Food consumption; Nutrition